2014
DOI: 10.3945/ajcn.113.071399
|View full text |Cite
|
Sign up to set email alerts
|

Obesity paradox in cancer: new insights provided by body composition

Abstract: The obesity paradox is present in cancer patients only when obesity is defined by BMI. Patients with sarcopenic obesity had the poorest prognosis. Cancer patients with high mortality risk can be identified by a body-composition assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
185
4
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(203 citation statements)
references
References 35 publications
8
185
4
6
Order By: Relevance
“…It is known that paradoxical obesity represents a good prognostic factor in the evolution of certain entities, such as in acute coronary syndromes, chronic heart failure, chronic renal disease and pneumonia (36)(37)(38)(39). Gruber et al described the concept of paradoxical obesity in 2002 by suggesting obesity as a good prognostic factor in patients undergoing percutaneous transluminal coronary angioplasty in short and long term (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that paradoxical obesity represents a good prognostic factor in the evolution of certain entities, such as in acute coronary syndromes, chronic heart failure, chronic renal disease and pneumonia (36)(37)(38)(39). Gruber et al described the concept of paradoxical obesity in 2002 by suggesting obesity as a good prognostic factor in patients undergoing percutaneous transluminal coronary angioplasty in short and long term (36).…”
Section: Discussionmentioning
confidence: 99%
“…Gruber et al described the concept of paradoxical obesity in 2002 by suggesting obesity as a good prognostic factor in patients undergoing percutaneous transluminal coronary angioplasty in short and long term (36). Recently, González et al (37) reported that ambulatory patients with cancer and sarcopenia (low rate of fat-free mass) have a higher risk of death. The few reports that include oncologic patients suggest that obesity is a factor to consider in the response to oncologic treatment, and in the progression and resolution of oncologic disease over the medium or long term (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been proposed that the obesity paradox may not be a true phenomenon, since large adipose tissue is frequently associated with large muscularity, which may be the real reason for the better outcome. To address this uncertainty, Gonzalez et al analysed the survival of cancer patients (22) . When stratified according to BMI, the longest survival was observed for those cancer patients with BMI > 25.…”
Section: Obesity Paradox In Cachexiamentioning
confidence: 99%
“…A low FFM has been linked to mortality in older and obese patients [19,20]. Thus, it would seem logical to consider that FFM at diagnosis may predict survival.…”
Section: Body Weight Versus Body Compositionmentioning
confidence: 99%